Hypoglycemic effect of the leaves and flowers of Geranium ayavacense L. “pasuchaca” on glycemia in Rattus rattus var. albinus - Gonzales Llontop, Luis Felipe (2021)
The hypoglycemic effect of the leaves and flowers of Geranium ayavacense L. “pasuchaca” on glycemia in Rattus rattus var. albinus and was referent to glibenclamide in an rat model. The male rats used were 240 grams of average weight. 24 animals were estimated in 04 lots of 06 each, fasting them and hyperglycemia was induced at a dose of 2 g of kg / p.c. glucose via orogastric route. Animals were randomized into four batches. The first batch of rats received 0.9% physiological saline, the second batch was given glucose, the third batch took glucose plus pasuchaca while the fourth batch received glucose plus glibenclamide. The pasuchaca dose used was 400mg / Kg. Glycemia was assessed at 4 lots at 0 ", 30", 60 ", 90" and 120 minutes. There were significant differences in the glycemic averages between the lots analyzed and verified by ANOVA at 5% significance (p <0.05). In our experimental conditions, the dose given of an infusion of Geranium ayavacense L. “pasuchaca” at 400mg / Kg over the blood glucose of Rattus rattus var. albinus did  how a hypoglycemic effect.